1999
DOI: 10.1002/chin.199931054
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Antiinflammatory Activity of Some New 6‐Methoxy‐α‐methyl‐2‐naphthalene Acetic Acid Derivatives.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Additionally, several derivatives exhibited enhanced selectivity in COX-2 inhibition when compared to felbinac [8]. Many similar studies have also indicated that the inclusion of a heterocyclic moiety containing nitrogen atoms may ameliorate gastric tolerability while broadening the anti-inflammatory spectrum of compounds [9,10].…”
Section: Introductionmentioning
confidence: 95%
“…Additionally, several derivatives exhibited enhanced selectivity in COX-2 inhibition when compared to felbinac [8]. Many similar studies have also indicated that the inclusion of a heterocyclic moiety containing nitrogen atoms may ameliorate gastric tolerability while broadening the anti-inflammatory spectrum of compounds [9,10].…”
Section: Introductionmentioning
confidence: 95%
“…Solution phase techniques are, however, limited to short reaction sequences that either use reagents in stoichiometric quantities, or use reagents that can be easily separated from the final products (Patrick, 2003;Terret, 1998). Various derivatives of 1,2,4-triazole are known to exhibit pharmacological properties like antibacterial, antifungal anticancer, anti-viral, anti-inflammatory, CNS depressant and anticonvulsant activity (Amir and Azam, 2004;Amir et al, 1999;Banachiewicz et al, 2004, ColanceskaRagenovic et al, 2001, Metwally et al, 2007, Mishra et al, 1991Parmar et al, 1972;Ravi and Rajkannan, 2004). In this work, focus is mainly on combinatorial synthesis and high throughput screening of 1,2,4-triazole derivatives (shown in Scheme 1 and Table 1) and identification of hits for antifungal activity by 2D deconvolution analysis.…”
Section: Introductionmentioning
confidence: 99%